Habilidades sociais: o que pensam os professores de alunos com deficiência no ensino regular - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2020)
This research, entitled “Social Skills: What do teachers of students with disabilities think in regular education”, was developed in a Municipal Elementary School in the municipality of Santarém-PA, seven teachers who have students with disabilities included. The objective was to understand the cognitions of elementary school teachers who work in regular classes with students with disabilities on social skills. Specifically, it aimed to: I - Characterize the sociodemographic data of teachers; II - Identify the social skills that teachers consider important to be developed in students with disabilities; III - Understand teaching cognitions about the teacher's role in the development of social skills of students with disabilities. The research is characterized as qualitative, field, exploratory and descriptive. The instruments for data collection used were: sociodemographic questionnaire and semi-structured interview. The data were analyzed using descriptive and technical statistics from the Collective Subject Discourse (CSD) respectively. The results showed that teachers have common sense knowledge about Social Skills, assigning a concept sometimes outside theoretical knowledge, showing that there are many challenges for acting within the school, especially with regard to the development of social skills. On the other hand, participants understand that such skills are important and contribute to the development of children, which can provide better learning, emphasize the relationship between family, colleagues and school for a better performance of the HS of students with and without disabilities , there is a need for training social skills for these teachers as they show interest in participating in a continuing education course aimed at developing social skills within the school context, with an emphasis on students with disabilities, as they believe that this audience can develop better with learning such social skills.
Keywords: Cognição docente; Habilidades sociais; Pessoa com deficiência; CNPQ:: Lingüística, Letras e Artes; Formação humana em contextos formais e não formais na Amazônia